Treatment of Two Cats with Advanced Nasal Lymphoma with Orthovoltage Radiation Therapy and Systemic Chemotherapy - dos Santos Cunha, Simone Carvalho; Corgozinho, Katia Barão; Ferreira, Ana Maria Reis (Acta Scientiae Veterinariae, 2016)
Background: Feline nasal lymphoma is generally a localized and radiosensitive tumor. Treatment options include radiation therapy, chemotherapy, or a combination of both treatments. Chemotherapy alone is generally not effective, leading to median survival times of 98 to 358 days, while RT alone or a combination of RT and chemotherapy lead to median survivals of 19 months and 955 days, respectively. Orthovoltage radiation therapy, the only radiation available in Brasil, has the disadvantage of being superfcial, treating only tumors of 2 cm or less and causing marked skin side effects. The objective of this paper is to report two cases of advanced feline nasal lymphoma, with cribriform plate destruction and central nervous system invasion, successfully treated with orthovoltage radiation therapy and systemic chemotherapy. Case: Two female mixed breed cats were presented with nasal discharge, sneezing and facial deformity. The second cat also had neurologic signalment. Defnitive diagnosis in histopathology was lymphoma. Computed tomography revealed advanced disease in both cases, with intranasal mass, bone lysis, invasion of orbital space and central nervous system. Both cats were treated with radiation therapy combined with chemotherapy. The frst case received radiation therapy for gross disease (12 daily fractions of 300 cGy, fve times per week) and CCNU/prednisolone chemotherapy, while the second case received cytoreductive rhinotomy followed by radiation therapy (12 fractions of 300 cGy in a Monday-Wednesday-Friday schedule) and chemotherapy with COP protocol. Both cats had long term tumor control, superior to 1000 days. Radiation side effects were well tolerated and resolved with supportive treatment. Chemotherapy side effects was neutropenia, only observed in the frst cat. One cat is still alive and in remission (1120 days after treatment), while the second cat died of unrelated cause (with no local tumor relapse) after 1011 days. Discussion: Radiation therapy could be considered the mainstay of treatment for feline nasal lymphoma. However, given that lymphoma is generally a systemic disease, chemotherapy should also play a role in management of feline nasal lymphoma. In the current report, both radiation therapy and chemotherapy were prescribed as it was considered the most aggressive treatment option. All acute radiation therapy reactions (erythema, conjunctivitis and keratitis) resolved with supportive care in reported cats. The combination of therapies used in this case report resulted in extended progression free interval as well as survival times, of over 1000 days. This results exceedes survival times of cats with nasal lymphoma treated with chemotherapy alone or with prednisone alone. Megavoltage radiation has greater penetrability and is more effective in treating nasal tumors, particularly tumors located at greater depths from the skin surface. Orthovoltage radiation therapy has the disadvantage of being too superfcial, treating tumors of 2 cm or less, with more skin side effects. As orthovoltage radiation is the only radiation therapy available in Brasil, it was used in both cats of this report and is effcient for appropriate long term tumor control. The presence of cribriform plate destruction at the time of diagnosis was considered to be anegative prognostic factor for both PFI and survival. However, in the reported cats, PFI and survival times were superior to 1000 days, even with cribriform plate destruction and central nervous system invasion. Feline nasal lymphoma should be aggressively treated by radiation therapy combined with systemic chemotherapy. These cats can beneft from long term tumor control and excellent quality of life after treatment. Keywords: feline, nasal lymphoma, radiation therapy, chemotherapy, survival.